WOUND HEALING POTENTIAL OF NAUCLEA LATIFOLIA AND MANIHOT ESCULENTA LEAF EXTRACTS IN TYPE 1DIABETIC RATS - Ajayi, Ebenezer Idowu O.; Popoola, Gbemisola; Ojediran, Edward (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: This study was designed to ascertain this claim and to investigate the possible mechanism of action in relation to their phytochemicalcontents, using crude extracts of N. latifolia and M. esculenta leaves on topical wound in a rat model of Type 1 diabetes.Methods and Materials: The leaves were air-dried under shade and subjected to cold extraction in 95% ethanol. Normoglycaemic male Wistar ratswere subjected to 2-month high-energy diet/ fat emulsion manipulation and injected with alloxan (150 mg/kg BW/day, i. p.). Fasting plasma glucosewas determined after 7 days and rats with values exceeding 200 mg/dl were selected. 16 diabetic rats (120 – 180 g) were randomly assigned to fourgroups of four animals each. Wound was inflicted on the back of each rat by excision method. The crude extracts were topically applied over a periodof 21 days. The scar tissues were removed at 7 days interval for collagen quantification and wound margin reduction was also monitored usingtracing paper.Results: The crude extracts showed efficient wound healing activity as revealed by increased collagen content (scar tissues versus fresh woundtissues ab initio). Percentage wound closure also progressed significantly (p< 0.05) upon topical application of the extracts.Conclusion: The crude extract of N. latifolia leaves has proven to be more potent than that of M. esculenta in wound healing in Type I diabetic rats.It stimulated wound contraction and collagen formation, making it a promising natural product for further screening in search of new chemicalentities that can be useful in diabetic wound management.